Analisis Yuridis Terkait Penerapan Euthanasia Yang Dilakukan di Indonesia Berdasarkan Perspektif Hukum Pidana - Aura Syahranni; Donyuanalloh Azdy; Salsabilah Putri; Dita Cahyani Sudirman (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
As a result of the advancement of science and technology, which has had a significant impact on altering human life, patients or families can now request the assistance of a doctor or medical staff in order to hasten a loved one's demise. However, the request for death was made because there was no medical treatment that could foretell or lessen the patient's illness, all attempts to cure the patient by the doctor had failed, and the patient and his family were unable to pay for the patient's care. Based on the author's findings on euthanasia research, it can be concluded that both in terms of the legal order in Indonesia, the practice of euthanasia itself has not yet found a place for regulation to regulate both specifically and clearly. Whereas as explained in the discussion, even though there are various articles in various laws such as the Criminal Code and UUDNRI 1945 there are several articles that slightly intersect with euthanasia, regarding the existence of euthanasia in Indonesia, it still does not have a special place legally and legally . Whereas the implementation of euthanasia in Indonesia itself, there have been several cases of euthanasia that have occurred in Indonesia, and several of these cases in their application to the realm of the Courts in Indonesia have not been given space in practice, in contrast to several other countries which have legalized the practice of euthanasia, such as the Netherlands and America. However, in carrying out the euthanasia practice itself, there are several conditions for carrying out the euthanasia practice itself.